Pembinaan Kerohanian Anak Usia Dini Di Paud KB Kristen Little Jhosua: Pendekatan Tematik Mengenal Ciptaan Tuhan Hari Ke-1 Hingga Ke- 6 - Ariyanti Waruwu; Roarta Agustina Marpaung; Maria Anjelina Simanjuntak; Hestina Putri Lumbangaol; Piter Son Waruwu; Melina Agustina Sipahutar (Journal of Innovative and Creativity, 2025)
This study aims to describe the implementation and effectiveness of the Thematic Approach to Understanding God's Creation Days 1 to 6 in the spiritual development of early childhood education at Little Joshua Christian Preschool. The method used is qualitative descriptive, with observation, image media, and activity documentation. The results of the study indicate that the use of this thematic approach is very effective because it bridges the story of Creation with the sensory experiences of early childhood. Here, each day of creation (such as light and dark, water, plants, animals, and humans) is explored interactively and tangibly. Children show very positive and enthusiastic responses. This study found that the thematic approach to God's Creation is a useful and important approach for building strong Christian faith and fostering a character that appreciates the Creator's magnificent work in early childhood.